NOTES ON PAPUASIAN SAPINDACEAE: HARPULLIA MABBERLEYANA SP. NOV., HARPULLIA RHACHIPTERA AND LEPISANTHES MIXTA - Takeuchi, W. (Edinburgh Journal of Botany, 2011)
Harpullia mabberleyana W.N.Takeuchi (Sapindaceae) is described from historically unexplored environments in Papua New Guinea’s southern ranges. The new species can be instantly recognised by its simple leaves, the only Harpullia ever found with that character. New observations and occurrences are also reported for the rarely collected Harpullia rhachiptera and Lepisanthes mixta.